2005
DOI: 10.1158/0008-5472.can-05-0592
|View full text |Cite
|
Sign up to set email alerts
|

Side Population Is Enriched in Tumorigenic, Stem-Like Cancer Cells, whereas ABCG2+ and ABCG2− Cancer Cells Are Similarly Tumorigenic

Abstract: Recently, several human cancers including leukemia and breast and brain tumors were found to contain stem-like cancer cells called cancer stem cells (CSC). Most of these CSCs were identified using markers that identify putative normal stem cells. In some cases, stem-like cancer cells were identified using the flow cytometry-based side population technique. In this study, we first show that f30% of cultured human cancer cells and xenograft tumors examined (f30 in total) possess a detectable side population. Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
856
4
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 841 publications
(927 citation statements)
references
References 54 publications
61
856
4
6
Order By: Relevance
“…Consistent with these observations, we find that B80% of our purified CD44 þ PCa cells are of the CD44 þ /a2b1 hi /CD133 À tumor progenitor phenotype (Patrawala et al, unpublished observations). Our work (this study; Patrawala et al, 2005) and others' (Maitland et al, 2005), together, suggest that solid tumors such as PCa will likely contain multiple populations of tumorigenic cells, all of which will be able to give rise to tumors but with different efficiencies.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Consistent with these observations, we find that B80% of our purified CD44 þ PCa cells are of the CD44 þ /a2b1 hi /CD133 À tumor progenitor phenotype (Patrawala et al, unpublished observations). Our work (this study; Patrawala et al, 2005) and others' (Maitland et al, 2005), together, suggest that solid tumors such as PCa will likely contain multiple populations of tumorigenic cells, all of which will be able to give rise to tumors but with different efficiencies.…”
Section: Discussionsupporting
confidence: 67%
“…We have recently shown that the LAPC-9 tumors have B0.1% SP, which is about 1000 times more tumorigenic than the non-SP cells (Patrawala et al, 2005). In contrast, the highly purified ABCG2 þ (which mediates the SP phenotype in some cell types) PCa cell population has very similar tumorigenic potentials to the ABCG2 À cells (Patrawala et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7G) that the number of sarcospheres generated from vector and R248W/P72R cells in each passage remained consistent; however, R248W/P72R cells formed~2-fold sarcospheres than vector cells, demonstrating their higher in vitro self-renewing potential. In addition, in a colony-forming assay that correlates with self renewal [37], R248W/P72R cells formed more numerous and larger colonies than vector cells (Fig. 7H).…”
Section: P53-r248w/p72r-knockdown Affects the Expression Of Stem-cellmentioning
confidence: 96%